An Overview of the Challenges and Risks of Uterine Transplantation Operations - Kolosovaitė, Karolina; Bužinskienė, Diana (Lietuvos chirurgija, 2024)
Introduction. Uterus transplant surgery is the only treatment for restoring fertility in women with infertility due to uterine pathology. Uterine transplantation have progressed from animal experiments to successful human operations to now non-experimental clinical procedures used to treat infertility due to uterine pathology in women who wish to carry their newborns to term. Purpose. Taking into account the latest scientific literature, to describe the challenges and risks faced during uterus transplant surgeries and to review why these surgeries are still only a part of experimental medicine. Research material and methods. Publications were searched in Google Scholar, PubMed databases. Search keywords and their combinations: “uterus transplantation operations”, “living donor”, “ethical issues”, “complications of uterus transplant operations”. 29 articles corresponding to the topic of the work were selected and analyzed. Results. Currently, about 90 uterus transplantation operations have been performed, of which 80 were from living donors. The result of the operations is more than 46 successful births and live newborns. Of these, 24 births were premature. Currently, there are 59 living donor hysterectomies in the literature, 35 performed by laparotomy, 20 by robotic surgery, and 4 laparoscopically. The overall birth rate of newborns after uterine transplantation exceeds 80%. Conclusions. Uterus transplant surgeries redefine the possibilities of motherhood, improve women’s reproductive rights, and therefore give women who are infertile due to uterine pathology the opportunity to have a baby.